Never do anything ever : by Jamie Kelly - Benton, Jim. (New York : Scholastic, 2005)
Jamie Kelly shares with her diary her search for inner beauty, dealing with fund raising, and problems in Phys ed class.
Z
"Jim Benton's tales from Mackerel Middle School."
"Apple series"--Cover p. [4].
b
b
Keywords: Diaries -- Juvenile fiction; Middle schools -- Juvenile fiction; Conduct of life -- Juvenile fiction; Diaries -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Conduct of life -- Fiction; Humorous stories; Humorous fiction